The Infinite Retina - Cronin, Irena; Scoble, Robert; Wozniak, Steve (Packt Publishing, 2020)
A compelling and insightful look at the future of Spatial Computing, and how this cutting-edge technology is changing the way we do business across seven primary industries, and what it means for humanity as a whole. Key Features Discover how Spatial Computing is changing the face of technology Get a roadmap for the disruptions caused by Spatial Computing and how it will affect seven major industries Gain insights about the past, present, and future of technology from the world's leading experts and innovators Book Description What is Spatial Computing and why is everyone from Tesla, Apple, and Facebook investing heavily in it? In The Infinite Retina, authors Irena Cronin and Robert Scoble attempt to answer that question by helping you understand where Spatial Computing-an augmented reality where humans and machines can interact in a physical space-came from, where it's going, and why it's so fundamentally different from the computers or mobile phones that came before. They present seven visions of the future and the industry verticals in which Spatial Computing has the most influence-Transportation; Technology, Media, and Telecommunications; Manufacturing; Retail; Healthcare; Finance; and Education. The book also shares insights about the past, present, and future from leading experts an other industry veterans and innovators, including Sebastian Thrun, Ken Bretschneider, and Hugo Swart. They dive into what they think will happen in Spatial Computing in the near and medium term, and also explore what it could mean for humanity in the long term. The Infinite Retina then leaves it up to you to decide whether Spatial Computing is truly where the future of technology is heading or whether it's just an exciting, but passing, phase. What you will learn Look back at historical paradigms that changed the face of technology Consider how Spatial Computing could be the new technology that changes our lives See how Virtual and Augmented Reality will change the way we do healthcare Learn how Spatial Computing technology will lead to fully automated transportation Think about how Spatial Computing will change the manufacturing industry Explore how finance and retail are going to be impacted through Spatial Computing devices Hear accounts from industry experts on what they expect Spatial Computing to bring to their sectors Who this book is for The Infinite Retina is for anyone interested in the future of technology and how Augmented Reality and Spatial Comp ...
Online resource; Title from title page (viewed May 8, 2020)